Kebijakan Kolaboratif Pencegahan Peredaran Gelap Narkotika pada Sektor Pariwisata di Indonesia - Bentonius Silitonga (LPPM and Travel Operation Department Universitas Asa Indonesia, 2024)
The increasingly popular tourism industry does not only bring profits for the country's foreign exchange or income for local communities. One of the problems arising from the tourism sector is the presence of foreign tourists in camouflage carrying out illicit narcotics trafficking in Indonesia. Therefore, collaborative policies are needed to overcome this problem. The aim of the research is to examine collaborative strategic steps and synergy models between stakeholders in reducing the abuse and illicit trafficking of narcotics through the role of the tourism sector in managing the social and economic potential of communities in vulnerable areas and prone to narcotics and narcotics precursors.The research is qualitative in nature and was conducted through interviews, literature review, and documentation techniques. The results of implementing collaborative policies to prevent illicit narcotics trafficking in the tourism sector have not been implemented well. This is because implementing agencies are still running independently.The resulting new concept is a synergistic model of collaborative policy implementation by optimizing the roles of various stakeholders based on their respective duties and functions contributing to a collaborative program which called the Desa Wisata Bersinar Program.